1986
DOI: 10.1177/028418518602700415
|View full text |Cite
|
Sign up to set email alerts
|

The Acetabular Sector Angle of the Adult Hip Determined by Computed Tomography

Abstract: A new set of angles measured on standard axial CT images of the hip joint is defined. The angles provide information on the support of the femoral head from the anterior and the posterior part of the acetabulum. These angles have been measured in 82 adult hips, and correlated to a set of established parameters commonly measured at conventional roentgenography and on CT images of the hip joint. The defined angles may prove to be valuable in the total appreciation of hip joint function and stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
112
3
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(135 citation statements)
references
References 8 publications
11
112
3
9
Order By: Relevance
“…Sets of paired opposing radial angles subtended by the acetabular rim were summed in four principal directions. Similar angles measured by other investigators [1,51,65], and summation of analogous rim locations of our measurements showed comparable values ( Table 7). Regardless of the individual acetabular depth in our study, the wave-like rim profile with its depressions and prominences was a constant finding.…”
Section: Discussionsupporting
confidence: 91%
“…Sets of paired opposing radial angles subtended by the acetabular rim were summed in four principal directions. Similar angles measured by other investigators [1,51,65], and summation of analogous rim locations of our measurements showed comparable values ( Table 7). Regardless of the individual acetabular depth in our study, the wave-like rim profile with its depressions and prominences was a constant finding.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies using CT of human hips have measured the contours of the bony acetabulum [13], the relative coverage of the femoral head by the acetabulum in developmental dysplasia of the hip [1,2,5,7], and the contact pressure between the acetabulum and the femoral head [12]. However, these studies have focused on normal and dysplastic hips and did not directly visualize the articular cartilage using MR. Steppacher and colleagues [27] used MR radial sequences to examine protrusio, deep, and retroverted acetabula, finding that retroverted acetabula had smaller cartilage surfaces than deep and protrusio acetabula.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate assessment of acetabular version and anterior and posterior femoral head coverage can be difficult, and changes in patient positioning can lead to errors in measurement [4,24,45,48]. Two-dimensional CT studies have become an integral part of diagnosis and preoperative planning, especially when assessing deficiencies in the transverse plane [5,26,29,33,41,59].…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional CT studies have become an integral part of diagnosis and preoperative planning, especially when assessing deficiencies in the transverse plane [5,26,29,33,41,59]. They allow for assessment of acetabular version and anterior and posterior femoral head coverage, defined by acetabular sector angles [4,7,22]. Patient positioning has the potential to cause errors in measurements on CT studies just as it does with plain radiographs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation